A recurrent polyalanine expansion in the transcription factor FOXL2 induces extensive nuclear and cytoplasmic protein aggregation. Issue 12 (9th December 2004) - Caburet, S; Demarez, A; Moumné, L; Fellous, M; De Baere, E; Veitia, R A
Abstract : Blepharophimosis syndrome is an autosomal dominant disease characterised by eyelid malformations, associated or not with premature ovarian failure. It is caused by mutations in the FOXL2 gene, which encodes a forkhead transcription factor containing a polyalanine (polyAla) domain of 14 alanines. Expansions of the polyAla tract from 14 to 24 residues account for 30% of the reported mutations and lead mainly to isolated palpebral defects. We have transfected COS-7 cells with DNA constructs driving the expression of the wildtype and mutant FOXL2 proteins fused to the green fluorescent protein. The polyAla expansion was found to induce the formation of intranuclear aggregates and a mislocalisation of the protein due to extensive cytoplasmic aggregation. These findings were confirmed by immunofluorescence. Co-transfection experiments suggest that the wildtype and mutant proteins can co-aggregate. We propose that the mechanism for the molecular pathogenesis of the polyAla expansions of FOXL2 may be its mislocalisation concomitant with its inclusion into nuclear aggregates. This may diminish the pool of active protein. Potential effects of aggregation on cell viability are under study.